2021
DOI: 10.1503/cmaj.210529
|View full text |Cite
|
Sign up to set email alerts
|

Informing COVID-19 vaccination priorities based on the prevalence of risk factors among adults in Canada

Abstract: Concern about imbalances between the demand and the supply of vaccinations for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been raised, given worldwide demand, centralized manufacturing and limitations in the infrastructure for vaccine delivery and administration in Canada. The optimal strategy for vaccination allocation to maximize public health benefit in Canada is unclear. The first phase of Canada's vaccine rollout focused on those at the highest risk for being infected with or transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…While NACI is a national advisory body, vaccine delivery in Canada is primarily a provincial/ territorial responsibility. As a result, NACI recommendations met with variable implementation across the country [36,37]. In most jurisdictions, priority vaccination was largely based on age, a limited number of chronic medical conditions, and healthcare occupation despite the known impact of socio-demographic factors such as ethnicity and income [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While NACI is a national advisory body, vaccine delivery in Canada is primarily a provincial/ territorial responsibility. As a result, NACI recommendations met with variable implementation across the country [36,37]. In most jurisdictions, priority vaccination was largely based on age, a limited number of chronic medical conditions, and healthcare occupation despite the known impact of socio-demographic factors such as ethnicity and income [36].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, NACI recommendations met with variable implementation across the country [36,37]. In most jurisdictions, priority vaccination was largely based on age, a limited number of chronic medical conditions, and healthcare occupation despite the known impact of socio-demographic factors such as ethnicity and income [36]. See S1 Table : Prioritization of Populations (Supporting Information) for the NACI-recommended priorities and access timelines adopted in the jurisdictions.…”
Section: Resultsmentioning
confidence: 99%
“…All typical factors during ICU planning include area, region, bed strength and the quantity of labor required. An extremely resistant microbial system, airborne transmission, high death rates in ventilated pacients, the need for confidence of the health workers in the medical services and the safe removal of profoundly irresistible biomedical abuse from patients are further considerations of a special COVID ICU (McAlister, Bushnik, Leung, & Saxinger, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…( 7 ) With respect to the prevalence of those living with multimorbidity or multiple COVID-19 risk factors in Canada, a recent study found roughly one-third of Canadians lived with two or more established risk factors for severe COVID-19, which included a list of several common comorbidities. ( 8 )…”
mentioning
confidence: 99%
“…(7) With respect to the prevalence of those living with multimorbidity or multiple COVID-19 risk factors in Canada, a recent study found roughly one-third of Canadians lived with two or more established risk factors for severe COVID-19, which included a list of several common comorbidities. (8) Despite the high and growing prevalence of multimorbidity in Canada, it remains an understudied health problem and it has received inadequate attention during the COVID-19 pandemic. While evidence points to multimorbidity as a risk factor for SARs-CoV-2 infection and poor COVID-19 outcomes, most of the focus in Canada has centred on individual risk factors-particularly age and individual conditions.…”
mentioning
confidence: 99%